قولعث فهم جرح للقرلن عنث لدثني - Al-Mutairi, Mastora Raja Hojylan (Penerbit Universiti Kebangsaan Malaysia, 2023)
The research addresses the topic of "criticizing peers," referring specifically to scholars who are peers, not others who differ in scholarly rank. These peer scholars may occasionally criticize each other, either through speech or implication. Several examples and evidence are presented in the first section of the study. However, scholars did not pay much attention to this type of criticism, nor did they adopt it, examine it, or consider it as a clear and valid evidence as required in the rules of criticism and modification. Instead, they were keen on seeking various excuses for these peer scholars. This is evident in their various works where they mentioned diverse rules to clarify the reality of this type of criticism and how to control it, deal with it, and avoid spreading it among people. This was done out of respect for the saying of the Messenger of Allah, preventing any negative remarks, rejection, or diminishing the status of these peer scholars. Through research, four rules have been identified as follows: The first rule: The default regarding the criticizer and the criticized among peers is that they are just and trustworthy. The second rule: The origin of this type of criticism lies in human nature. The third rule: Criticism among peers should be concealed and not propagated. The fourth rule: The purposes of peer scholars in criticizing each other may not always be clear and understandable.